Optimized type 2 fuzzy logic control for low-speed vehicle pedal pressing automation using hybrid spiral sine cosine algorithm - Azrul Azim, Abdullah Hashim; Nor Maniha, Abdul Ghani; Salmiah, Ahmad; Mohd Ruzaini, Hashim; Noor Zirwatul Ahlam, Naharuddin; Addie, Irawan (International Islamic University Malaysia-IIUM, 2025)
This paper describes the systematic design and experimental analysis of a Fuzzy Logic Controller (FLC) to govern vehicle speed for low-speed driving by adjusting an attached linear actuator that governs the vehicle's pedal. The research investigates two FLC approaches: the standard Type 1 FLC and the advanced Type 2 FLC, both optimized using the Hybrid Spiral Sine Cosine Algorithm (SSCA). The integrated system linking the actuator to the dynamics model of the vehicle shows improved ability in the manner in which control is done. Physical modeling and simulation were done in Simscape MATLAB, which provides an opportunity for modeling and visual description of the actuator system's relationship with the dynamics of the car. The results presented in this paper prove the fact that the analyzed Type 2 FLC optimized by the SSCA method performs better than the traditional Type 1 FLC in terms of the key metrics, with improvements of 32.4242% in overshoot, 0.364 seconds in settling time, and a reduction of 0.002009 in steady-state error at 2 km/h reference speed. This superior performance highlights the potential of the SSCA-optimized Type 2 FLC to automate pedal pressing for vehicle speed control, effectively replacing repetitive pedal actions and reducing driver fatigue, as this mechanism proves capable of controlling vehicle speed with high precision.